The Importance of Vision Care and Rehabilitation Following Stroke. - Delly, Amber T. (Optometry & Visual Performance, 2021)
Background: Many people who have suffered a stroke can experience lasting effects that can impact their ability to partake in daily routines. Research supports that the visual system can be affected in many ways after enduring a stroke, which can ultimately limit independent function. In the optometric world, there are numerous ways to rehabilitate visual symptoms that restore the ability to participate in activities of daily living. Case Report: A 34-year-old wheelchair-bound Caucasian female presented for a vision therapy evaluation two years after an idiopathic left-sided cerebral vascular accident (CVA). The CVA affected her in many ways, such as: ability to move the right side of her body, capability to articulate language, and dysfunction of her binocular vision system. A multidisciplinary team was already established, which included physical, equine, and speech therapists to assist in her recovery process. Ocular examination findings revealed diagnoses of internuclear ophthalmoplegia, nystagmus, and convergence insufficiency. Vision therapy was initiated to rehabilitate visual issues, particularly diplopia, nystagmus, and helping her left eye to appear more opened. Throughout vision therapy, activities were modified in order for the patient to appreciate the same visual experiences as others not bound by a wheelchair. After completing 45 sessions of vision therapy, she only experienced diplopia in extreme right and left gazes, and she was able to stand with some assistance. Her multidisciplinary team were all on board to work towards her goal of being able to walk again independently. Conclusion: Enduring a stroke can affect a multitude of systems within an individual, which requires a multidisciplinary approach to regain useful function. Undesirable visual symptoms resulting from a stroke can cause valid concerns, including limitations to independence. Early treatment is recommended to help rehabilitate visual barriers. Slight modifications in vision therapy activities can offer the same visual experiences for those bound by a wheelchair as for those not so bound.